Photocatalytic Activity of Cellulose Nanocrystals/Zinc Oxide Nanocomposite Against Thiazine Dye under UV and Visible Light Irradiation - Rey Marc T. Cumba; Clark B. Ligalig; Jhea Mae D. Tingson; Meralin P. Molina; Arnold C. Alguno; Custer C. Deocaris; Felmer Latayada; Indah Primadona; Rey Yonson Capangpangan (ASEAN Journal of Chemical Engineering, 2022)
Organic dyes used in the food and textile industries are the primary sources of environmental contamination due to their high toxicity and nonbiodegradability. This paper describes the synthesis of cellulose nanocrystals/zinc oxide (CNC/ZnO) nanocomposite via the sol-gel method. Various characterization techniques such as FTIR spectroscopy, UV-Vis spectroscopy, and FESEM-EDX analysis were done. FTIR and UV-Vis analyses initially confirmed the formation of CNC/ZnO nanocomposites. FESEM-EDX showed a fiber-like structure with agglomerated particles on the CNC-ZnO image, suggesting the functionalization of ZnO nanoparticles onto the CNC. The photocatalytic potential of the CNC/ZnO nanocomposite was then evaluated by degrading 10 ppm thiazine dye (methylene blue) solution. The solution was irradiated with UV and visible light at an ambient temperature. The degradation was monitored at different time intervals using a UV spectrophotometer to measure the absorbance value intermittently. Results on the photocatalytic activity indicated that the synthesized CNC/ZnO nanocomposite showed faster degradation under UV light irradiation than the visible light, with an efficiency of 96.11% and 85.60%, respectively, after 180 mins of light irradiation. Further, the results suggest that the synthesized CNC/ZnO nanocomposite showed great promise as a sustainable material for the degradation of organic contaminants in an aqueous solution.